(untitled) (LIS TODAY, 2021)
This paper covers a brief introduction about mobile technology and its implementation in libraries. It describes how mobile technology can be used in different areas of library and its services to provide excellent services to its users. Further the paper describes mobile applications available for libraries and its users and some national and internationally renowned useful mobile based library applications, websites for creating mobile applications, mobile applications for users/learners etc.